Hubungan Pemakaian Kontrasepsi Hormonal Dengan Gangguan Menstruasi Di Puskesmas Kebonsari Kota Pasuruan - Pratnya Ilminingtyas (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
the design of this study is analyttical by using cross sectional approach, with the population of 40 acseptors of family planning on june 2008. sampling technique which isused is random sampling technique. in wich there are 37 respondents with the questionnairre on menstruation disturbance and contraception identity card in order to know the contraception used. the result of the study showed that the respondents which were using combination hormonal contraception and having menstruation disturbance was 7,69% and the respondents which were using non combination hormonal contraception and having menstrual disturbance was 72,73%. the menstrual disturbance (p,0,05) with the exact fisher test showed that there was a relation between the hormonal contraception user with the menstrual disturbance (p=0,00).